2015
DOI: 10.1088/0004-637x/809/2/171
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Modeling of Gamma-Ray Flares in Blazar Pks1510–089

Abstract: Here we present a new approach for constraining luminous blazars, incorporating fully timedependent and self-consistent modeling of bright γ-ray flares of PKS 1510-089 resolved with Fermi-LAT, in the framework of the internal shock scenario. The results of our modeling imply the location of the γ-ray flaring zone outside of the broad-line region, namely around ≃ 0.3 pc from the core for a free-expanding jet with the opening angle Γ θ jet ≃ 1 (where Γ is the jet bulk Lorentz factor), up to ≃ 3 pc for a collimat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 62 publications
0
44
0
Order By: Relevance
“…Such a scenario is consistent with the observed results from VLBI or VLBA (Bach et al 2005;Nesci et al 2005;Larionov et al 2013;Rani et al 2014Rani et al , 2015. In addition, twelve prominent sub-flares superimposed in the long-term trend may be related with shock/turbulence in jet (e.g., Marscher & Gear 1985;Marscher et al 2008Marscher et al , 2014Narayan & Piran 2012;Saito et al 2015;MAGIC Collaboration et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Such a scenario is consistent with the observed results from VLBI or VLBA (Bach et al 2005;Nesci et al 2005;Larionov et al 2013;Rani et al 2014Rani et al , 2015. In addition, twelve prominent sub-flares superimposed in the long-term trend may be related with shock/turbulence in jet (e.g., Marscher & Gear 1985;Marscher et al 2008Marscher et al , 2014Narayan & Piran 2012;Saito et al 2015;MAGIC Collaboration et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These observations reveal a complex multi-wavelength behaviour [1,2] with changing correlation patterns between different wavelengths. This has lead to different interpretations, such as the requirement of at least two radiative emission components [3], or two spatially distinct emission zones [4].…”
Section: Introductionmentioning
confidence: 81%
“…Orienti et al (2013) found a γ-ray flare from PKS 1510-089 in late 2011 after the onset of a strong radio flare and located the γ-ray emitting site to be about 10 pc downstream of the jet base. On the other hand, Saito et al (2015) suggested that the γ-ray flares in 2011 occurred at the distance of 0.3-3 pc from the central engine with the seed photons provided by the BLR and DT, based on the model of internal shocks formed by colliding blobs of the jet plasma. Aleksić et al (2014) showed the HE and VHE γ-ray spectra in 2012 smoothly connected with each other.…”
Section: Introductionmentioning
confidence: 99%